APLICATION MHETODOLOGY SMED IN FOOD INDUSTRIE: redutions of setup time and impact on production efficiency - Prudencio, Orlando; Tosoni Decarlis Rodrigues Neto, José Benedito (Revista Interface Tecnológica, 2025)
The market has demanded constant change and adaptation from organizations, as it is necessary to meet customer requirements for an increasingly larger and more diverse range of products. Reducing setup time is an essential task to increase productive efficiency and competitiveness in the food industry. In this context, the SMED methodology emerges as an efficient and effective solution to reduce machine idle times and optimize the flexibility of production lines, ensuring that process standardization improve the quality of the final products. Thus, the objective of this study was to analyze and explore the application of the SMED methodology in the food industry, its benefits, and challenges. The method applied was bibliographic, with an analysis of academic article databases, specialized magazines, websites, and scientific papers. The results of this study indicate that the investments required for the implementation of SMED lead to significant productivity gains and substantial cost reductions, transforming into competitive and strategic advantages for the company within the food industry.